Hubungan penerapan pendidikan karakter Terhadap perilaku sosial siswa - Cecillia - Nova; Jumaini - -; Ganis - Indriati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The aim of this research was identify the correlation between implementation of character education with social behavior of students. The design of the study was correlation research with cross sectional approach. The sampling technique was consecutive sampling with 94 students who attend school in Vocational High School Pekanbaru State 2 were selected based on inclusion criteria. Instrument used the study was a questionnaire consisted of 20 question to asses implementation of character education and 26 question to asses social behavior of students which was valid and reliable. Data analyses used in the study were univariate analysis to know distribution of frequency and bivariate analyses by using chi square. The result showed that p value (0,054) < alpha (0,10). It meant that there was a correlation between implementation of character education with social behavior of students. Educational institutions are expected to be able to optimize the implementation of character education efforts in schools to increase student achievement and to minimize deviant behavior of students. Keywords : implementation of character education, social behavior